Blue Rubber Bleb Nevus Syndrome - Nanayakkara, P R; Samarasekera, D. N. (The Sri Lanka Medical Association, 2007)
ntroduction Blue rubber bleb naevus syndrome (BRBNS) is a rare clinical entity characterised by multiple haemangiomas commonly occurring in the skin and the gastrointestinal (Gl) tract. The association between these cutaneous cavernous haemangiomas and similar lesions in the U l tract was first described in 1860 and the acronym BRBN S was given by Bean in 1958 [ l J, Patients may present with massive GI bleeding or anaemia due to chronic occult bleeding.
Keywords: multiple haemangiomas